Limited TTP supply affects telomere length regulation in a telomerase-independent fashion - Toussaint, Martin (Oxford University Press, 2005)
An adequate supply of nucleotides is essential for DNA replication and DNA repair. Moreover, inhibition of TTP synthesis can cause cell death by a poorly characterized mechanism called thymine-less death. In the yeast Saccharomyces cerevisiae, the genes encoding thymidylate synthetase (CDC21) and thymidylate kinase (CDC8) are both essential for de novo TTP synthesis. The effects of temperature-sensitive mutations in these genes have been characterized and, curiously, the phenotypes displayed by cells harboring them include shortened telomeric repeat tracts. This finding raised the possibility that the enzyme telomerase is very sensitive to TTP-pools. We tested this possibility in vivo by assessing telomerase-dependent extension in situations of lowered TTP supply. The results show that the above-mentioned short telomere phenotype is not a consequence of an inability of telomerase to elongate telomeres when TTP synthesis is impaired. Moreover, this telomere shortening was abolished in cells harboring a mutation in DNA polymerase α. Previously, this same mutation was shown to affect the coordination between conventional replication and telomerase-mediated extension. These results thus re-emphasize the importance of the interplay between conventional replication and telomerase-mediated addition of telomeric repeats in telomere replication.